2014
DOI: 10.1371/journal.pone.0105345
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Membrane Accommodation to Thermal Oscillations in the Coral Seriatopora caliendrum

Abstract: In the present study, the membrane lipid composition of corals from a region with tidally induced upwelling was investigated. The coral community is subject to strong temperature oscillations yet flourishes as a result of adaptation. Glycerophosphocholine profiling of the dominant pocilloporid coral, Seriatopora caliendrum, was performed using a validated method. The coral inhabiting the upwelling region shows a definite shift in the ratio of lipid molecular species, covering several subclasses. Mainly, the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Other metabolic processes enhanced by algal symbiosis include biosynthesis of the neurotoxins 69 , γ-glutamyl-β -cyanoalanine and γ-glutamyl-β-aminopropionitrile , biosynthesis of plasmanylcholine and metabolism of thiamine (vitamin B1). Plasmanylcholine is involved in acclimation to a temperature-fluctuating environment in Screlactinian corals 70 (Fig. 3 , Supplementary Figs S18 – S20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Other metabolic processes enhanced by algal symbiosis include biosynthesis of the neurotoxins 69 , γ-glutamyl-β -cyanoalanine and γ-glutamyl-β-aminopropionitrile , biosynthesis of plasmanylcholine and metabolism of thiamine (vitamin B1). Plasmanylcholine is involved in acclimation to a temperature-fluctuating environment in Screlactinian corals 70 (Fig. 3 , Supplementary Figs S18 – S20 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our investigation, the lower content of DGCC and lower UI of structural lipids in S. hystrix may serve to acclimate to high temperature environments by adjusting cell membrane structure. Previous investigations showed that Seriatopora caliendrum could adapt to the upwelling region with strong temperature oscillations by adjusting the content and saturation of phosphatidylcholines and plasmanylcholines [37]. As for the biological functions of the newly identified phospholipids, they is still unknown.…”
Section: Regulation Of Immune Response Cellular Membrane Structure An...mentioning
confidence: 98%
“…Mechanisms responsible for physiological acclimation are not well understood, but the process is likely affected by thermal history 23 , 24 . Corals can resist temperature stress or acclimate to dramatic temperature fluctuations 25 28 . Interestingly, coral-associated bacterial communities also exhibit a similar phenomenon.…”
Section: Introductionmentioning
confidence: 99%